Aspectos operacionais de revestimentos soldados: desgaste erosivo e cavitação - Silva, Hebert Roberto da (2014)
The process of MIG/MAG welding with its your applications using two wires pointing in the market as an alternative to coating when high productivity is desired. Potential variants emerge from this process as MIG/MAG cold wire and MIG/MAG double wire. One of the biggest difficulty is the setting of its parameters, which in addition to duplicate compared to conventional MIG/MAG, act in a dependent manner. A greater understanding of this technology applied to coatings on turbines in various positions is critical so that you can master the process and its variables, aiming to enhance the application in industry. It was proposed in this study an experimental evaluation to verify the influence of some variables on the profile of cord and wear resistance. For this it is proposed in this thesis to make deposits with weld metal AWS 308LSi stainless steel and alloys of cobalt (Stellites 6 and 21) plates in carbon steel SAE 1020 in flat and horizontal positions. In the characterization of wear in the lining was used the determination of the hardness and surface topography. It is concluded that cobalt alloys have superior resistance to erosive damage with emphasis on the Stellite 21 alloy in erosion and cavitation in Stellite 6. In an intermediate position with respect to wear are mixtures of austenitic stainless steel and cobalt alloys. Therefore it is essential to study welding processes with multiple wires as proposed in this thesis aiming the best combination of alloys for resistance to cavitation-erosion phenomena.